Impact of particle nonsphericity on the development and properties of aerosol models for East Asia. (January 2015) - Chen, Hao; Cheng, Tianhai; Gu, Xingfa; Wu, Yu
Abstract: In this paper, the effects of aerosol nonsphericity information on the classification of aerosol models and the associated radiative properties over East Asia are investigated. The radiance measurements and inversions of the Aerosol Robotic Network (AERONET) are used. Four aerosol models over East Asia are obtained by adding the shape information to the clustering analysis. These four aerosols are identified on the basis of their optical properties. Compared to the results without sphericity parameter, adding the sphericity parameter in the clustering process contributes to the extraction of a strongly absorbing aerosol. Furthermore, the effect of the physical and optical properties of the aerosol on the top of atmospheric (TOA) total reflectance and polarized reflectance are investigated. The results indicate that the addition of the sphericity parameter in the clustering process leads to a change in the total reflectance by up to 16% and a change in the polarized reflectance by up to 100%. Highlights: Impact of particle nonsphericity on the aerosol models clustering is studied. Aerosol models exhibit significant changes considering the shape information. Difference of aerosol models due to shape affects the aerosol remote sensing.